MOTIVATIONAL FACTORS, TECHNICAL FACTORS DALAM PEMANFAATAN ATAS ADOPSI E-GOVERNMENT: Peranan Intention To Use - Shelomitha Moza Azhari, (2022)
E-Government is a digital communication tool between the government and the public. The use of information and communication technology in government service processes is used to increase efficiency, effectiveness, transparency, and accountability in the implementation of public services. The purpose of this study is to test and prove the influence of motivational factors and technical factors on the utilization of E-Government adoption with mediating variables of intention to use. The sample in this study was 525 people who use E-Government in Indonesia. The reliability and validity of the questionnaire have been thoroughly tested. Meanwhile. This study used Structural Equation Modeling (SEM) techniques to analyze data with the help of the SmartPLS 3.0 application. The results showed that perceived benefits, socio-cultural, functional qualities of the system, previous experience, perceived simplicity, technical qualities of the system have a significant influence. Meanwhile, awareness and ICT Infrastructure do not have a significant influence. Then, the intention to use does not link the influence between variable motivational factors and technical factors on utilization over the adoption of E-Government.